EGFR expression level Predicts Response and Overall Survival in Gastric Cancer PDTX model Treated with Cetuximab - Xiao-Hong Wang; Lian-Hai Zhang; Jia-Fu Ji (临床与病理杂志; 卷 35, 编号 1 (6 2015), 2026)
Objective: The aim of this study was to determine whether the EGFR statuscould significantly predict some benefit in overall survival and response to cetuximab in advanced GC xenografts. Methods: Two hundred xenografts derived from 20 GC patients were established. Then they were divided into cetuximab treated group and control group randomly. Results: Among the cetuximab treated group, 4 GC cases were identified responded to cetuximab.Those cetuximab treated PDX models had longer OS than non-treated. High EGFR mRNA expression and immunohistochemistry score are more prone to response to cetuximab. EGFR amplification, mRNA and protein overexpression were associated with the OS in cetuximab treated PDX models. Moreover, in the PDX models derived from EGFR amplification, mRNA or protein overexpression cases, the OS is significantly different between the cetuximab treated and control group, while the OS in not statistically different in other cases. Conclusion: EGFR status predicts sensitivity to therapy and survival in GC treated with cetuximab, especially the mRNA and protein expression level.